Inadvertent Transfusion of Two Incompatible Blood Units: A Case Report - Salarian, Sara; Bagheri, Bahador; Darban, Mahboubeh; Shakeri, Alireza (Novelty in Biomedicine, 2023)
Background: An incompatible blood transfusion may lead to hemolytic transfusion reactions and severe complications such as intravascular hemolysis, multiorgan failure, and even death. Prevention, early diagnosis, and treatments have the main roles to decrease transfusion complications. Cases Report: We present a case of a 43-year-old woman with a history of mandibular malignancy and facial reconstruction surgery who needed to blood transfusion due to a hemorrhage around her tracheostomy, and inadvertently 2 units of incompatible blood were transfused. The errors conduce to this issue and consideration to prevent and manage incompatible blood transfusions are discussed. Conclusion: This case showed that an effective technique for recognizing and avoiding transfusion mistakes is staff awareness of the potential errors at the bedside and in the laboratory. Furthermore, patients’ immunological status, early detection, and recognition of blood transfusion manifestation are critical factors for early diagnosis and treatment.